Tauroursodeoxycholic acid exerts anticholestatic effects by a cooperative cPKCα-/PKA-dependent mechanism in rat liver. Issue 10 (26th June 2008) - Wimmer, R; Hohenester, S; Pusl, T; Denk, G U; Rust, C; Beuers, U
Abstract : Objective: Ursodeoxycholic acid (UDCA) exerts anticholestatic effects in part by protein kinase C (PKC)-dependent mechanisms. Its taurine conjugate, TUDCA, is a cPKCα agonist. We tested whether protein kinase A (PKA) might contribute to the anticholestatic action of TUDCA via cooperative cPKCα-/PKA-dependent mechanisms in taurolithocholic acid (TLCA)-induced cholestasis. Methods: In perfused rat liver, bile flow was determined gravimetrically, organic anion secretion spectrophotometrically, lactate dehydrogenase (LDH) release enzymatically, cAMP response-element binding protein (CREB) phosphorylation by immunoblotting, and cAMP by immunoassay. PKC/PKA inhibitors were tested radiochemically. In vitro phosphorylation of the conjugate export pump, Mrp2/Abcc2, was studied in rat hepatocytes and human Hep-G2 hepatoma cells. Results: In livers treated with TLCA (10 μmol/l)+TUDCA (25 μmol/l), combined inhibition of cPKC by the cPKC-selective inhibitor Gö6976 (100 nmol/l) or the non-selective PKC inhibitor staurosporine (10 nmol/l) and of PKA by H89 (100 nmol/l) reduced bile flow by 36% (p<0.05) and 48% (p<0.01), and secretion of the Mrp2/Abcc2 substrate, 2, 4-dinitrophenyl- S -glutathione, by 31% (p<0.05) and 41% (p<0.01), respectively; bile flow was unaffected in control livers or livers treated with TUDCA only or TLCA+taurocholic acid. Inhibition of cPKC or PKA alone did not affect the anticholestatic action of TUDCA. Hepatic cAMP levels and CREB phosphorylation as readout of PKA activity were unaffected by the bile acids tested, suggesting a permissive effect of PKA for the anticholestatic action of TUDCA. Rat and human hepatocellular Mrp2 were phosphorylated by phorbol ester pretreatment and recombinant cPKCα, nPKCϵ, and PKA, respectively, in a staurosporine-sensitive manner. Conclusion: UDCA conjugates exert their anticholestatic action in bile acid-induced cholestasis in part via cooperative post-translational cPKCα-/PKA-dependent mechanisms. Hepatocellular Mrp2 may be one target of bile acid-induced kinase activation.